The role of natural gas in a low-carbon Europe: Infrastructure and regional supply security in the global gas model - Franziska Holz; Philipp M. Richter; Ruud Egging (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
In this paper, we use the Global Gas Model to analyze the perspectives and infrastructure needs of the European natural gas market until 2050. Three pathways of natural gas consumption in a future low-carbon energy system in Europe are envisaged: i) a decreasing natural gas consumption, along the results of the PRIMES model for the EMF decarbonization scenarios; ii) a moderate increase of natural gas consumption, along the lines of the IEA (2012) World Energy Outlook's New Policy Scenario; and iii) a temporary increase of natural gas use as a bridge technology, followed by a strong decrease after 2030. Our results show that import infrastructure and intra-European transit capacity currently in place or under construction are largely sufficient to accommodate the import needs of the EMF decarbonization scenarios, despite the reduction of domestic production and the increase of import dependency. However, due to strong demand in Asia which draws LNG and imports from Russia, Europe has to increasingly rely on pipeline exports from Africa and the Caspian region from where new pipelines are built. Moreover, pipeline investments open up new import and transit paths, including reverse flow capacity, which improves the diversification of supplies. In the high gas consumption scenario similar pipeline links are realized-though on a larger scale, doubling the costs of infrastructure expansion. In the bridge technology scenario, the utilization rates of (idle) LNG import capacity can be increased for the short period of temporary strong natural gas demand.
Keywords: Q31; Q47; Q54; C61; D43; 330; natural gas; climate change; infrastructure; equilibrium modeling